2016
DOI: 10.1890/15-0033
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower (Helianthus annuus) pollination in California's Central Valley is limited by native bee nest site location

Abstract: A major challenge in habitat restoration is targeting the key aspects of a species' niche for enhancement, particularly for species that use a diverse set of habitat features. However, restoration that focuses on limited aspects of a species' niche may neglect other resources that are critical to population persistence. We evaluated the ability of native plant hedgerows, planted to increase pollen and nectar resources for wild bees in agricultural landscapes, to provide suitable nesting habitat and enhance nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 45 publications
(59 reference statements)
1
40
0
1
Order By: Relevance
“…Nearby natural or seminatural habitat, such as rangelands, have been suggested as potential nesting habitat (Kremen et al ). Adjacent agricultural fields could have also provided nest site locations (Kim et al ; Sardiñas et al , in press). Alternately, foraging species could have been nesting in our study sites but were undetected by e‐traps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearby natural or seminatural habitat, such as rangelands, have been suggested as potential nesting habitat (Kremen et al ). Adjacent agricultural fields could have also provided nest site locations (Kim et al ; Sardiñas et al , in press). Alternately, foraging species could have been nesting in our study sites but were undetected by e‐traps.…”
Section: Discussionmentioning
confidence: 99%
“…For all models we used model validation procedures to ensure that the models were not overdispersed and did not have inflated type I error rates (Ives ; Sardiñas et al , in press). We included only female bees of ground‐nesting species in all analyses (both nesting and foraging) because male bees are not indicative of nesting rates and may only be resting in vegetation (Kim et al ).…”
Section: Methodsmentioning
confidence: 99%
“…We used 1.96-square-foot emergence traps (BugDorm, MegaView Science, Taiwan) to sample nesting bees (Sardiñas and Kremen 2014;Sardiñas et al 2016). …”
Section: Bee Samplingmentioning
confidence: 99%
“…Soil moisture, however, may be correlated to a number of other conditions, including soil compaction (Xie et al 2013). In the sunflower study system, generalist wild bees have been found to nest both within crop fields as well as along un-irrigated field edges (Sardiñas et al 2016). Soil moisture may not exert as strong of effects as other characteristics that affect nest site selection and nesting success of generalists, while sunflower specialists may be better adapted to the within field conditions where sunflowers are grown.…”
Section: Soil Moisture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation